2020
DOI: 10.30534/ijatcse/2020/6091.42020
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Service Quality Elements towards the Overlapping IT Framework Process on the IT Hardware Support Services (ITHS)

Abstract: Many large organizations use the information technology (IT) service processes to deliver IT services within the service level agreement (SLA). In order to support and expand the business, an organization needs to be able to promise reliable and effective information technology (IT) Service Quality. Nevertheless, each of the IT frameworks has many components and processes. This is difficult for the organization as it involves management commitment, complicated process diagrams, general work instructions, it do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
1
5
0
Order By: Relevance
“…Ahmad et al [12]. The issue of overlaps within the processes of ITG is corroborated by the findings of the study [13], which indicates that about 25% of the activities involved are found in at least two of the three main IT frameworks.…”
Section: Introductionsupporting
confidence: 53%
“…Ahmad et al [12]. The issue of overlaps within the processes of ITG is corroborated by the findings of the study [13], which indicates that about 25% of the activities involved are found in at least two of the three main IT frameworks.…”
Section: Introductionsupporting
confidence: 53%
“…Further research and practical case studies are needed to explore the full potential and best practices for integrating Agile into IT audit frameworks (Al Faruq, et. al., 2020, Bin Ahmad, Ibrahim & Bin Ngah, 2020, Samiei & Habibi, 2021.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many financial institutions rely on legacy IT systems and infrastructure, which may be outdated, inefficient, and difficult to integrate with modern technologies (Al Faruq, et. al., 2020, Bin Ahmad, Ibrahim & Bin Ngah, 2020, Samiei & Habibi, 2021. Upgrading and modernizing these systems while maintaining operational continuity presents a significant governance challenge.…”
Section: Understanding It Governancementioning
confidence: 99%
“…In the rapidly evolving landscape of financial institutions, effective IT governance plays a pivotal role in ensuring operational efficiency, regulatory compliance, and risk mitigation (Al Faruq, et. al., 2020, Bin Ahmad, Ibrahim & Bin Ngah, 2020, Samiei & Habibi, 2021. With the increasing reliance on technology to deliver financial services, the need for robust IT governance frameworks has become paramount .…”
Section: Introductionmentioning
confidence: 99%